DEVELOPMENT OF ENVIRONMENTAL COMPETENCES OF SPECIALISTS FROM THE INTERNATIONAL HOTEL AND TOURISM BUSINESS - Semyrga, L.I.; Khomyn, V.R.; Kaziuka, N.P.; Humeniuk, V.V. (The actual problems of regional economy development, 2023)
The article examines the elements of environmental competences that can be formed in specialists in the international hotel and tourism business using an interdisciplinary approach. The need to assess the knowledge, skills, and abilities necessary for successful work in the field of hotel and tourism business from the point of view of environmental responsibility is substantiated. Normative acts, institutional norms and rules that regulate the activities of hotel and tourism enterprises in the environmental sphere were analyzed, which made it possible to clarify conceptual structures related to environmental responsibility in the hotel and tourism business. On the basis of surveys of practitioners, the level of awareness of representatives of the hotel and tourism business with the issue of environmental responsibility, the application of environmental practices in the hotel business was determined; thanks to the observation of the work of hotels and the operation of resorts, the issue of responsible management of waste, energy and water resources, and natural territories was revealed. The formation of professional competences among specialists under the bachelor's educational program "International Hotel and Tourism Business" of the Ivano-Frankivsk National Technical University of Oil and Gas in environmental responsibility of the hotel business, which consists in the ability of hotels and other hospitality establishments to care for the environment and reduce the impact of their activities, is substantiated on nature and resources, to regulate the process of ensuring the balanced development of the hotel and tourist industry, to ensure the economic, social and ecological development of the territories. A structural and logical scheme for the formation of competencies of future specialists in the international hotel and tourism business has been developed; the asymmetry of the Green Key hotel industry on the map of Europe is considered; the problems hindering the further development of ecological tourism are described; the factors of achieving sustainable development of the hotel and tourist business are singled out; measures are identified that can help the hotel reduce its impact on the environment and create more competitive catering services due to the environmental factor. Based on the study of international experience, it has been proven that the presence of sustainable practices in hotels not only benefits the environment, but also improves the economic and social behavior of tourists, increases the morale of the staff and contributes to the long-term success of the hotel.